2019
DOI: 10.4028/www.scientific.net/kem.816.19
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Glass Fibers for Polymer Composites

Abstract: The paper gives a brief description of carbon and glass fibers used to obtain polymer composite materials with high thermal, physical and mechanical characteristics. Some methods for surface activation of carbon and fiberglass, which will be used to increase the adhesion interactions at the fiber-polymer boundaries, are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This problem can be solved by their filling with additional components, in particular reinforcing CF. [22][23][24][25] Typical wear mechanisms of the CFreinforced polymer composites are fiber breakages, [26][27][28] interfacial delamination along the fiber-matrix interfaces, [29][30][31][32] the matrix failures, and so forth. [33][34][35] The results of the published data analysis have shown that damages of the composites under tribological loading are typically initiated at interphase boundaries, especially when there is a significant difference in the chemical nature and the physical morphology between the matrix and the fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be solved by their filling with additional components, in particular reinforcing CF. [22][23][24][25] Typical wear mechanisms of the CFreinforced polymer composites are fiber breakages, [26][27][28] interfacial delamination along the fiber-matrix interfaces, [29][30][31][32] the matrix failures, and so forth. [33][34][35] The results of the published data analysis have shown that damages of the composites under tribological loading are typically initiated at interphase boundaries, especially when there is a significant difference in the chemical nature and the physical morphology between the matrix and the fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Loading with the solid lubricants often reduces the mechanical properties of the polymer composites, including wear resistance. This problem can be solved by their filling with additional components, in particular reinforcing CF 22‐25 . Typical wear mechanisms of the CF‐reinforced polymer composites are fiber breakages, 26‐28 interfacial delamination along the fiber‐matrix interfaces, 29‐32 the matrix failures, and so forth 33‐35 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, some research results have been published [ 19 , 20 , 21 , 22 ] on designing antifriction PI-based composites with low friction coefficients and improved wear resistance due to loading with PTFE, SiO 2 and WS 2 nanoparticles, etc. A partial decrease in mechanical properties is compensated by loading with reinforcing fibers, primarily carbon or glass ones [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier works [8][9][10], the CF surface was subjected to various types of treatment in order to increase its "affinity" for the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%